A recognition method for crack position on the outer ring of full ceramic bearing based on the synchronous root mean square difference. (22nd December 2021) - Liu, Z.M.; Bai, X.T.; Shi, H.T.; Wu, Y.H.; Ma, H.
Abstract: In this paper, a method for recognizing the crack location on the outer ring of the full ceramic bearing is proposed, which considers the transmission of the vibration signal on the outer ring when a crack occurs. A two-degree-of-freedom nonlinear dynamic model of the full ceramic bearing with a crack is established, and the impact of the crack is evaluated through the change of the strain energy. Then, considering the attenuation of the vibration signal along the outer ring, the dynamic model is improved with a time-varying stiffness related with the crack position. By analyzing the ratio of the synchronous root mean square difference of the vibration signal, the position of the outer ring crack is recognized. The simulation results are compared with the experimental results to verify the accuracy and feasibility of the position recognition method. The research provides a new recognition method for bearing fault location, and helps with the fault diagnosis and status monitoring of bearing systems.